2021
DOI: 10.1371/journal.pone.0257094
|View full text |Cite
|
Sign up to set email alerts
|

A predictive analysis on the risk of peste des petits ruminants in livestock in the Trans-Himalayan region and validation of its transboundary transmission paths

Abstract: Although the Trans-Himalayan region (THR) is an important endemic and rendezvous area of peste des petits ruminants (PPR), monitoring and prevention measurements are difficult to execute because of the rough geographical conditions. Besides, a heterogeneous breeding system and the poor veterinary service of susceptible animals compound the existing problems. Here, we propose a forecasting system to define the key points of PPR prevention and aid the countries in saving time, labor, and products to achieve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 68 publications
(81 reference statements)
0
51
0
Order By: Relevance
“…This helped to address problems associated with spatial sampling biases. Ideally, filtering or thinning removes the fewest records necessary to substantially reduce the effects of sampling bias, while simultaneously retaining the occurrence points with the greatest amount of useful information [ 30 , 31 ]. The geo-coordinates were then saved in a comma-separated value (CSV) format and imported into ArcGIS (version 10.6 ESRI) for editing and projected in UTM-WGS-1984 with standard settings or resampling to 30 arc-seconds.…”
Section: Methodsmentioning
confidence: 99%
“…This helped to address problems associated with spatial sampling biases. Ideally, filtering or thinning removes the fewest records necessary to substantially reduce the effects of sampling bias, while simultaneously retaining the occurrence points with the greatest amount of useful information [ 30 , 31 ]. The geo-coordinates were then saved in a comma-separated value (CSV) format and imported into ArcGIS (version 10.6 ESRI) for editing and projected in UTM-WGS-1984 with standard settings or resampling to 30 arc-seconds.…”
Section: Methodsmentioning
confidence: 99%
“…It therefore seems clear that sharing borders with endemic countries located outside of the considered area likely plays a role in PPR introduction. For instance, a predictive analysis study recently suggested the existence of several epidemiological corridors between China and neighbouring endemic countries, such as India, Nepal, Bhutan and Bangladesh, and proposed transhumance and the presence of susceptible wildlife as factors likely contributing to PPR transmission and maintenance in the Trans-Himalayan region [ 36 ]. Using a similar least-cost path (LCP) modelling approach for transboundary PPR movement, epidemiological linkages were predicted between China and Pakistan, India, Kazakhstan and Tajikistan [ 37 ].…”
Section: Ppr Situation At Regional Levelmentioning
confidence: 99%
“…In addition, the filtering program plays the role of systematic sampling. It can delete adjacent records to reduce spatial aggregation, which is regarded as the most effective method in correcting sampling bias [36,37].…”
Section: Anthrax Occurrence Data and Preprocessingmentioning
confidence: 99%
“…In addition, the human population density from the Asia Continental Population Datasets (2000-2020), which are publicly and freely available both through the WorldPop Dataverse Repository and the WorldPop project website (http://www.worldpop.org.uk/data/), were used as predictor variables in this research. Principal component analysis (PCA) was used to reduce the number of continuous environmental variables [37,42,43]. During PCA, we used eigenvalues larger than 0.97 and the scree plot criterion for PCA in item level factoring [44].…”
Section: Environmental Variables and Preprocessingmentioning
confidence: 99%